Karakteristik sifat fisik dan pH tanah pada lahan percobaan Manggoapi Fakultas Pertanian Universitas Papua Manokwari - Elius Hilungka; Samsul Bachri; Siti Hadjar Kubangun; Samen Baan (Agrotek, 2020)
This study aimed to identify the physical properties and soil pH of theManggoapi field experimental area, Faculty of Agriculture, which is being used bystudents, lecturers, or researchers for experimental activities of agricultural cultivation. Theresults found that the color of the soil ranges from dark brown to dark yellowish brown andthe soil color between the top layer and the bottom layer has blended due to frequent usedfor cultivation. Soil texture ranges from slightly coarse, medium and fine grades. The soilstructure ranges from globular, angular to granular lumps of medium to fine size, withmoderate to weak stability. The consistency of the soil is rather sticky and somewhatplastic, having a firmness that is loose to very loose. Surface rock is spread between 0-25%and rock outcrop 0-45%, with good drainage, and effective depth is more than 15.5 – 64.5cm. Soil pH is classified as neutral to alkaline.